THE STRONG SEQUENTIAL NUMBER OF GRAPHS - Ichishima R.,; Muntaner-Batle F.A.,; Oshima A., (Utilitas Mathematica, 2020)
Abstract. In this paper, we introduce the notion of strong sequen¬tial number, and provide a necessary condition for a graph to have finite strong sequential number as well as sufficient conditions for a graph to have infinite strong sequential number. We also exhibit the connections between the strong sequential number and other param¬eters that have previously been studied in the area of graph labelings. In addition, we present some results involving joins of graphs. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.